Islam kejawen as an adoption of local wisdom and Islamic development in Javanese communities - Soenjoto, Wening Purbatin Palupi (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This paper explains Islam Kejawen as the adoption of local wisdom learned from generation to generation by the Javanese community. Influenced by Hindu and Buddhist teachings. Then the acculturation process becomes a part of the belief called Kapitayan. After the arrival of saints in Java, the spread of the religion Islam still maintains the existing ritual culture, such as through songs and puppets. Islam is spread in the form of simple teachings of the recognition of God without removing hereditary rituals carried out by Javanese communities before. Both are verycoherent after Islam and Java united in one religious and spiritual bond. It seems as if it cannot be distinguished which is Javanese culture and which is Islam. Then the mixing of these two, or well-known as syncretism, became a form and characteristic of Islam in Java. Because in general, the syncretism between Islam and the local culture has entered various lines of life in multipleregions. However, based on socio-geographical conditions, we can be more observant ofthe intensity of the spread of the mixing of Islamic and Javanese teaching.